PEMBENTUKAN, PERKEMBANGAN DAN PEMBAHARUAN HUKUM ISLAM DALAM TINJAUAN ORIENTALIS - Fakhruddin, Fakhruddin (De Jure: Jurnal Hukum dan Syari'ah, 2009)
The development of Islamic law from its inception to its maturity has drawn a lot of attentions from some well known figures within Western scholars. Great names, such as Goldziher, Schacht, and Anderson, are among those who contribute the discourses on Islamic law in classical and modern period. While the first two scholars focus their research on Islamic law in the early phase of its development, the last one direct his study on its development in the modern period. The role of Quran and Sunnah on the development of Islamic law is under critical analysis of the Goldziher and Schacht, while the reform of it becomes the center of Anderson’s study.Perkembangan hukum Islam mengundang perhatian para tokoh pemikiran barat seperti Ignaz Goldziher, Schacht and Anderson. Mereka adalah tokoh-tokoh yang berkontribusi terhadap kajian-kajian hukum Islam pada periode klasik dan modern. sementara Goldziher dan schacth memfokuskan penelitian mereka pada hukum Islam pada fase awal perkembangannya, Anderson fokus pada hukum Islam periode modern. Peran al-Quran dan Sunnah terhadap perkembangan hukum Islam menjadi bahasan utama dari analisa kritis Goldziher dan Schacht sedangkan pembaharuan hukum Islam menjadi kajian Utama dari Anderson.Keywords: Orientalis, Pembaharuan, Hukum Islam